Advantages of simultaneous bilateral trabeculectomy over consecutive bilateral trabeculectomy in lbadan (1996)
A retrospective study of 26 patients who underwent simultaneous bilateral trabeculectomy over a 5year period was reviewed. Advantages of simultaneous bilateral trabeculectomy include a shorter stay in hospital compared to consecutive bilateral trabeculectomy, as well as a single general anaesthetic if required and this reduces the risk of exposure to anaesthetic agents within a short time. The turn-around time in theatre is also improved compared with separate operations. Preoperatively, 20 of the patients (77%) were on two or more antiglaucoma therapy. 69% of the patients (18patients) spent 7days in hospital, from admission to discharge, the normal duration of hospital stay for unilateral trabeculectomy. Only 31% spent over one week, none stayed in hospital beyond two weeks. Post operative complications occurred in 8 eyes (15.4%) but none led to blindness. Visual outcome was good in these patients as none had reduced vision postoperatively compared to preoperatively, 3eyes had an improvement in visual acuity postoperatively.